2009
DOI: 10.1016/j.jvs.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

In vivo human lower extremity saphenous vein bypass grafts manifest flow mediated vasodilation

Abstract: Objective As in arteries, venous endothelium modulates vessel homeostasis and tone. The effect of an arterialized environment on venous endothelial function remains poorly understood. In particular, regulation of saphenous vein graft (SVG) blood flow and lumen caliber remains undefined. We hypothesized that mature SVGs would exhibit endothelium-dependent, flow-mediated vasodilation. We further hypothesized that endothelium-derived nitric oxide (NO) was an important mediator of vascular tone. Methods Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…The implantation of a vein graft into arterial circulation often results in the development of IH, leading to vessel stenosis (Owens et al, 2009;Owens, 2010). This process is associated with the dedifferentiation of HSMCs, which turn from a contractile to a secretory phenotype, characterized by increased proliferation and migration (Owens et al, 2004;Mitra et al, 2006;Alexander and Owens, 2012;Nguyen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of a vein graft into arterial circulation often results in the development of IH, leading to vessel stenosis (Owens et al, 2009;Owens, 2010). This process is associated with the dedifferentiation of HSMCs, which turn from a contractile to a secretory phenotype, characterized by increased proliferation and migration (Owens et al, 2004;Mitra et al, 2006;Alexander and Owens, 2012;Nguyen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These distributions of proliferative plaque formation are different from the atherosclerotic lesions induced by hyperlipidemia, which is mainly located in both the aorta and carotid arteries. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Flow-mediated vasodilation was performed according to current guidelines and standards 36,37 as already described by our group 38 and other investigators 39 . Subjects were asked to fast (≥ 8 hours) and be free of nicotine (≥ 4 hours).…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Several studies have demonstrated that C-reactive protein (CRP) and other inflammatory markers, including interleukin-6 (IL-6) and intercellular-adhesion-molecule-1 (ICAM-1), are elevated in patients with PAD. 46 Inflammation increases the risk of progression to PAD and of its severity, 710 and more importantly, is a predictor of increased mortality in patients with PAD. 1113 …”
Section: Introductionmentioning
confidence: 99%